Peranan Pemerintah dan Optimalisasi Sektor Pertanian dengan Sinergitas Lembaga Keuangan Mikro Syariah-Agribisnis dan Agriculture Trust Fund - Zuhairan Y. Yunan; Heri Permana; Devina Aprilia; Fikri Abdullah (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2020)
Agriculture is the strategic sector in sustainable national economic development structure. This is due to agriculture has various natural resources that can be managed for long term. Agriculture also become the growth centre and main effort in fulfilling the needs in rural areas. But, this sector has some cultural obstacle such as infrastructure, lack of market knowledge, technology application, and capital problem. Agricultural sector also has high dependency on climate and natural changes like volcanic eruption, flood, and drought which foil agricultural product,damage infrastructure, and cause big economic losses for most farmer. There are so many agricultural threat that put farmer in poor situation and trapped in multiplied debt as the result of the absence of attention to farmer’s life in Indonesia. Some program and government policy like agriculture insurance and previous agricultural financial support is not enough to build and empower the agricultural sector. By that reason, the writer has an idea to develop Agribusiness- based Micro Syari’ah Financial Institution, sinergized with Agriculture  Trust Fund and Government as the best solution to solve all problem in agricultural sector. This research is also purposed to show the concept of creating friendly Financial Institution for the farmer from financing side and giving partnership to the farmer in applying the technology and selling the harvest product including educative protection if crop failure happens. This research uses qualitative descriptive approaching method by using secondary data sources such as literature from previous research and articles from mass media. The result of this research is the sinergy between Agribusiness-based Micro Syari’ah Financial Institution, Agriculture Trust Fund, and Government can move the economy and also contribute to financial inclusion for sustainable rural economics by giving business financing, partnership, and development along with protection in crop failure in order to increase farmer life standard and strengthen national food security. Keyword: Cultural obstacles, agricultural threat, financial inclusion, Agribusiness-based Micro Syari’ah Financial Institution.